The relationship between physical activity and procrastination behavior among Chinese university students: a chain mediated effect of body self-esteem and overall self-esteem - Zhuan, Sunyoumeng; Cao, Jinjin; Ye, Yongheng; Li, He; Zhang, Qinqin; Wang, Xin (Frontiers in Public Health, 2024)
Objective This study aimed to explore the relationship between physical activity and procrastination behavior among college students and the serial mediating roles of body self-esteem and overall self-esteem. Methods A cross-sectional survey was conducted involving 1,018 college students. The Physical Activity Rating Scale, the College Students’ Physical Self-perception Profile, the Self-Esteem Scale, and the Chinese Procrastination Scale were utilized. Serial mediating effect analysis and Bootstrap analysis were applied to the data. Results (1) Individuals engaging in high levels of physical activity demonstrated significantly lower levels of procrastination behavior compared to those with moderate or low levels of physical activity (Partial η2 = 0.01, F = 2.762, p < 0.01). (2) Physical activity was positively correlated with body self-esteem (r = 0.37, p < 0.01) and overall self-esteem (r = 0.29, p < 0.01), and negatively correlated with procrastination behavior (r = −0.14, p < 0.01). body self-esteem was positively correlated with overall self-esteem (r = 0.11, p < 0.01) and negatively correlated with procrastination behavior (r = −0.13, p < 0.01). Overall self-esteem also showed a significant negative correlation with procrastination behavior (r = −0.26, p < 0.01). (3) Mediation effect analysis indicated that body self-esteem and overall self-esteem played partial mediating roles in the relationship between physical activity and procrastination behavior among college students. The mediating effects were composed of three pathways: “Physical Activity → body self-esteem → Procrastination Behavior,” “Physical Activity → Overall Self-Esteem → Procrastination Behavior,” and “Physical Activity → body self-esteem → Overall Self-Esteem → Procrastination Behavior,” with the effect sizes accounting for 27.70, 12.26, and 7.28% of the total effect, respectively. Conclusion The findings of this study lead to several key conclusions regarding the relationship between physical activity, self-esteem, and procrastination behavior among college students. Firstly, engagement in moderate levels of physical activity is more effective in reducing procrastination behavior among college students. Secondly, participation in high volumes of physical activity is associated with increased levels of both body self-esteem and overall self-esteem. Lastly, physical activity not only directly impacts procrastination behavior but also indirectly influences it by enhancing body self-esteem and overall self-esteem, thereby further reducing the individual’s level of procrastination. These conclusions suggest that physical activity plays a multifaceted role in mitigating procrastination behavior in college students. By promoting self-esteem, physical activity can foster a positive psychological state that is conducive to proactive behavior and academic success. The study’s findings underscore the importance of integrating physical activity into college students’ daily routines as a strategy to combat procrastination and enhance self-esteem.